Social representations of HIV/AIDS among seropositive pregnant women* - Freire, Daniela de Aquino; Oliveira, Thais da Silva; Cabral, Juliana da Rocha; Angelim, Rebeca Coelho de Moura; Oliveira, Denize Cristina de; Abrão, Fátima Maria da Silva (Revista da Escola de Enfermagem da USP, 2021)
Objective: To identify the representational contents of pregnant women living with HIV. Method: Exploratory, descriptive, qualitative study, conducted with pregnant women with HIV from August 2017 to January 2018. Semi-structured interview was opted for. The IRAMUTEQ software was used for analysis, organizing the data into 2 blocks: a) moment of discovery, impacts, representational contents of HIV; and b) representational contents in living with the disease. Results: The participating pregnant women amounted to 25. Initially, the social representation of HIV translated the representation of death; however, this construction changes as women understand information of the pathology, which starts to be seen as a disease which demands more care. Conclusion: The conception of HIV as frightful is mainly due to concern about transmission to the fetus. The resignification of HIV was perceived among pregnant women, which favors new behaviors and attitudes towards the representational contents related to a deeper knowledge about the virus, demystifying the idea that this is a deadly disease.